Comparison of Heavy Metals and Arsenic Species in Seaweeds Collected from Different Regions in Korea - Ka Jeong Lee; Eun Hye Kang; Minchul Yoon; Mi Ra Jo; Hongsik Yu; Kwang Tae Son; Sang Hyeon Jeong; Ji Hoe Kim (Applied Sciences, 2022)
We evaluated the levels of heavy metals and arsenic (As) species in 11 different types of seaweed collected from major coastal cities in Korea. The concentration ranges of heavy metals in the seaweed were as follows: cadmium (0.023–0.232 mg/kg fresh weight [fw]), and lead (0.025–0.222 mg/kg fw), with most meeting international regulations for edible seaweeds. The amount of total As, however, was high, ranging from 1.020 to 20.525 mg/kg fw. Especially in the case of Sargassum seaweed, the fraction of inorganic As, including arsenate (As [V]) and arsenate (As [III]), which have potent toxicity, ranged from 5.198 to 16.867 mg/kg fw, while other seaweeds, such as Pyropia sp., Enteromorpha sp., Undaria sp., and Saccharina sp., predominantly contained a non-toxic organic As (i.d. arsenosugars). Multivariate analysis revealed that the Sargassum genus group had high levels of inorganic As. Sargassum seaweeds had a high fraction of inorganic As, but most of them are considered inedible seaweeds. Of these, Sargassum fusiforme (hijiki) is widely recognized as an edible seaweed, but the average daily intake is quite low based on statistical data from Asian countries and S. fusiforme is considered a safe food when eaten at the recommended daily intake.